PELATIHAN E-COMMERCE DAN MANAJEMEN KEUANGAN SEBAGAI LANGKAH MENINGKATKAN PENDAPATAN PADA KERIPIK PISANG ARJUNA - Ira Vahlia; Nina Lelawati (LPPM Universitas Andalas, 2019)
Era of all-use ICT today, it also requires small-scale industry players to improve their capabilities in the field of information communication and technology. The internet creates a business environment that no longer emphasizes time and distance. Based on the background of the problems faced by the home industry of arjuna banana chips; 1) Banana arjuna chips home industry in terms of marketing the products produced have not utilized online sales by using e-commerce. 2) Home industry of arjuna banana chips has not done a good bookkeeping in its production activities. As for the goal of service is; 1) Partners are given e-commerce training, this is done for partners to market their products to the general public through ICT. 2) Partners are given assistance, this activity aims to enable partners to book all activities specifically related to their financial entry and exit. The training and service that has been carried out concluded that PKM activities carried out through training and mentoring to partners of arjuna banana chips are able to innovate initially conventional marketing into marketing that utilizes technological developments, namely by doing electronic marketing or also called E-commerce.